FORCED INTERNAL DISPLACEMENT OF THE UKRAINIAN POPULATION: RISKS RAISED BY WAR - Malynovska, Olena; Yatsenko, Liubov (Стратегічна панорама, 2024)
The large-scale war forced millions of Ukrainians to leave their homes in search of safety. The mass displacement of the population led to an increase in the level of uncertainty and raised risks for both individuals and the whole of society. This article aims to assess the scale of internal migration in Ukraine during the war and to investigate the impact of this phenomenon on the quantitative and qualitative characteristics of the labor potential and the possibilities of its use. Our assessment of the number of internally displaced persons (IDPs), and our examination of the state of their adaptation and integration in the new territories of residence are based on administrative data about the registration of citizens as IDPs provided by social services as well as the surveys and research findings by international organizations and domestic sociological institutions. We present an overview of individual challenges and risks raised by the forced displacement of the population, and highlight the specific features of their manifestation. In particular, we single out an increase in the demographic burden, a decrease in the number of people of reproductive age, a reduction in the number of jobs, an increase in the burden on the budget, a drop in labor productivity, a loss or reduction in the income of a large part of the population, a limit of access to quality social services, as well as unemployment, deterioration of the quality of employment, increased social vulnerability, and weakening of social cohesion. Risks increase the probability of negative changes that lead to uncertainty, deterioration of the demographic situation, weakening of the stability of the economy, decline in the level and quality of life of the population, deepening of social inequality, growth of social tension, decline in the consumption capacity of the population, complete or partial loss of social ties and jobs. We offer recommendations regarding priorities and specific measures of the national state policy aimed at avoiding risks and minimizing their possible consequences. The implementation of this policy should be focused on establishing legal, economic, and institutional frameworks for easing tensions in the areas of material security and employment, improving the demographic situation as well as the quality and availability of social services, and improving living conditions.